Safety and tolerability of rifaximin for the treatment of irritable bowel syndrome without constipation: a pooled analysis of randomised, double‐blind, placebo‐controlled trials. Issue 10 (3rd April 2014) - Schoenfeld, P.; Pimentel, M.; Chang, L.; Lembo, A.; Chey, W. D.; Yu, J.; Paterson, C.; Bortey, E.; Forbes, W. P.
Summary Background The efficacy of rifaximin, a nonsystemic, gut‐targeted antibiotic for reducing non–constipation‐predominant irritable bowel syndrome (non‐C IBS) symptoms, has been demonstrated in one phase 2b and two phase 3 randomised, double‐blind, placebo‐controlled trials, but detailed data about rifaximin safety and tolerability during treatment and subsequent follow‐up periods are lacking. Aim To assess and determine the frequency of rifaximin and placebo adverse events (AEs) in phase 2b and phase 3 non‐C IBS trials. Methods A post hoc pooled safety analysis of the phase 2b (rifaximin 275, 550, and 1100 mg twice daily for 2 weeks; 550 mg twice daily for 4 weeks) and phase 3 (rifaximin 550 mg three times daily for 2 weeks) studies was performed. Data on treatment and post‐treatment AEs were collected. Patients were followed up for 12 weeks and 10 weeks post‐treatment in the phase 2b and phase 3 trials, respectively. Results Patients receiving rifaximin (n = 1103) and placebo (n = 829) had a similar incidence of drug‐related AEs (12.1% vs. 10.7%), serious AEs (1.5% vs. 2.2%), drug‐related AEs resulting in study discontinuation (0.8% vs. 0.8%), gastrointestinal‐associated AEs (12.2% vs. 12.2%) and infection‐associated AEs (8.5% vs. 9.5%). There were no cases of Clostridium difficile colitis or deaths. Conclusions The safety and tolerability profile of rifaximin during treatment and post‐treatment was comparable to placebo. Future research should define the safety and tolerability profile, including risk of C. difficile colitis and microbial antibiotic resistance, with repeated courses of rifaximin in patients with non—constipation‐predominant irritable bowel syndrome (ClinicalTrials.gov: NCT00269412, NCT00731679, and NCT00724126).